IMPLEMENTATION OF DISCLOSURE PRINCIPLE TOWARDS PUBLIC COMPANIES: JURIDICAL ANALYSIS ON LAW NO. 8 YEAR 1995 AND PERPU NO. 1 YEAR 2020 - Fennieka Kristianto; Fidela Gracia (President University, 2021)
The development of a country is influenced by several sectors which include the economic sector and it is considered to be one of the most essential factors in the growth or 3development of the country. The development of Indonesia itself is known to be immensely affected by economic growth. This economic growth is likewise running and participated by a lot of parties from Indonesia as well as foreign parties which are obtained through their investment here in Indonesia. One of the most influential parties within economic growth is the capital market itself which functions to help business actors. However, due to the current situation caused by the pandemic COVID-19, the Indonesian Government issued a Regulation of The Government in place of Law No. 1 in the year 2020 concerning Kebijakan Keuangan Negara dan Stabilitas Sistem Keuangan Untuk Penanganan Pandemic Corona Virus Disease 2019 (COVID-19) dan/atau Dalam Rangka Menghadapi Ancaman Yang Membahayakan Perekonomian Nasional dan/atau Stabilitas Sistem Keuangan (hereinafter referred to as PERPU COVID-19). As this regulation is implemented it raises several issues regarding the relevant existing law. The research method that is enforced within this journal is analytical normative research, this research is a general exploration that is likely aiming to execute legal aspects functioning as a prescriptive order, and in this method, the law from the stance of the norms will be inspected. This research is fulfilled through the implementation of a statute approach that is completed by evaluating the relevant laws and regulations relating to the issues set forth within this research. This journal will analyze the applicable regulations, as well as the contradictory matters, that arise from PERPU COVID-19 about the disclosure principle towards public companies.Keywords: Disclosure Principle, Emiten, Public Company, Capital Market, Capital Market Law.Article History